Sports Nutrition and Gross Motor Skill Development in Youth Athletes: A Literature Review - Setyo Purwanto; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
This study explores the relationship between sports nutrition and gross motor skill development in young athletes, focusing on maintaining optimal nutrition levels. The primary issue identified is the lack of understanding of how nutrition impacts gross motor skills and athletic performance in children and adolescents. This study explores the relationship between sports nutrition and gross motor skill development in young athletes. The study aims to analyze how nutritional strategies affect gross motor skill development and overall health in young athletes. A qualitative descriptive research model, informed by a comprehensive literature review, was used. Literature was collected from reputable scientific databases using keywords such as "Sports Nutrition," "Gross Motor Skills," and "Youth Athletes." Data from ten relevant articles were analyzed to identify the impact of nutritional strategies on motor skill development. Results indicate that optimal nutrition plays a crucial role in enhancing gross motor skills, such as running, jumping, and coordination, which are essential for athletic performance. Macronutrients—carbohydrates, proteins, and fats—support energy levels, muscle growth, and recovery, while micronutrients like vitamins and minerals contribute to cognitive function and overall well-being. The study also reveals that socioeconomic factors affect access to nutritious food and motor skill outcomes. The conclusion underscores the importance of balanced nutrition for motor skill development and athletic performance. Recommendations for future research include employing longitudinal study designs to establish causal relationships, exploring synergistic effects of nutrients, and examining socioeconomic factors more deeply. Additionally, integrating nutrition education with physical training could offer practical solutions to enhance motor skill development in young athletes